2015
DOI: 10.3390/ijerph120404256
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Link Between Public Transit Use and Active Commuting

Abstract: Background: An established relationship exists between public transportation (PT) use and physical activity. However, there is limited literature that examines the link between PT use and active commuting (AC) behavior. This study examines this link to determine if PT users commute more by active modes. Methods: A volunteer, convenience sample of adults (n = 748) completed an online survey about AC/PT patterns, demographic, psychosocial, community and environmental factors. t-test compared differences between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 44 publications
3
12
0
Order By: Relevance
“…Variables entered as potential confounders based on their known associations with transit-use and physical activity ( Bopp et al, 2015 , Brown et al, 2015 , Lachapelle et al, 2016 , Lachapelle and Pinto, 2016 , Miller et al, 2015 ) were self-reported in the participant questionnaire. These included age, sex, race/ethnicity (white, Hispanic, black, and other [American Indian or Alaskan Native, Native Hawaiian or other Pacific Islander, Asian or East Indian, and other]), body mass index (BMI [weight in kilograms/height in meters 2 ]), automobile ownership, residence type (single family, multi-family, other), household income (“low income” < 200% of the Federal Poverty Threshold [FPT]; and “not low income”, greater than or equal to 200% FPT), educational level (no high school or GED, high school or GED, and some college or more).…”
Section: Methodsmentioning
confidence: 99%
“…Variables entered as potential confounders based on their known associations with transit-use and physical activity ( Bopp et al, 2015 , Brown et al, 2015 , Lachapelle et al, 2016 , Lachapelle and Pinto, 2016 , Miller et al, 2015 ) were self-reported in the participant questionnaire. These included age, sex, race/ethnicity (white, Hispanic, black, and other [American Indian or Alaskan Native, Native Hawaiian or other Pacific Islander, Asian or East Indian, and other]), body mass index (BMI [weight in kilograms/height in meters 2 ]), automobile ownership, residence type (single family, multi-family, other), household income (“low income” < 200% of the Federal Poverty Threshold [FPT]; and “not low income”, greater than or equal to 200% FPT), educational level (no high school or GED, high school or GED, and some college or more).…”
Section: Methodsmentioning
confidence: 99%
“…Those with better access to public transit were more likely to have higher rates of self-reported physical activity and active commuting. Bopp et al (2015) used a similar methodology for commuters in the mid-Atlantic region of the United States. The study revealed that public transit was the most significant predictor of active commuting status.…”
Section: Health Physical Activity and Transitmentioning
confidence: 99%
“…Although activity is most frequently considered within a recreational context, physical activity can be classified into four domains of life describing how people spend their time including active transportation (AT), such as walking, biking or using public transportation (PT) [ 8 ]. AT, with PT, is considered a strategic and integral pathway to improving physical activity levels and thus reducing overweight/obesity levels [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Since travel is essential to daily living, the level of physical activity involved with PT is particularly significant because PT users typically walk or bike on the origin, destination or both sides of their transit stops [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%